(untitled) (Journal of Health, Population and Nutrition, 2010)
This study was undertaken to determine the genetic diversities of Giardia intestinalis isolated in Thailand. G. intestinalis cysts were collected from stool samples of 61 subjects residing in Bangkok or in rural communities of Thailand with and without gastrointestinal symptoms. All the cyst samples gave positive tpi amplicons (100% sensitivity), either of the 148- or the 81-bp tpi segments. Cyst assemblage identification of the 148- and 81-bp tpi gene segments by polymerase chain reaction showed that 8% of the cysts were assemblage A, 41% assemblage A and B combined, and 51% assemblage B. The prevalence of assemblage A was significantly lower than that of assemblage B and the mixed types. Restriction fragment length polymorphism (RFLP) of the 384-bp ß-giardin gene segment revealed that 12% and 88% of the assemblage A cysts were AI and AII respectively. RFLP, based on the 432-bp gdh gene segment, showed 45.5% of the assemblage B cysts to be BIII and 54.5% to be BIV. The AI sub-assemblage was less prevalent than the others. All subjects with AI and 50% of the subjects with BIII sub-assemblage cysts were symptomatic; 80% of symptomatic Bangkok residents were adults/elderly while 85% of the rural cases were children. Key words: ß-giardin; Genotyping; Giardia duodenalis; Giardia intestinalis; Giardiasis; Glutamate dehydrogenase; Triose phosphate isomerase; Thailand DOI: 10.3329/jhpn.v28i1.4522 J Health Popul Nutr 2010 Feb; 28(1):42-52